Labour and Body Violence: Women's Saga from Jharia Colliery to West Virginia Colliery. Issue 1 (June 2017) - Sinha, Jyoti
Women workers in the Indian coal mines have never been a homogenous category. Caste affiliations, class status, tribal background, regional and local belongings all play a role both in forging collective solidarities (or lack thereof) as well as women's own observations of their life and work. The social dynamics between different rungs of employment are at times conciliatory, but often contentious. In the absence of dissenting solidarity, the major concern of women are not larger issues but their personal issues and struggles at the everyday level, which reflect their individual agency. The narratives of mineworkers even as they reveal caste/class as well as political differences nonetheless underscore the extraordinary hardship women experience regardless of their social location. This article would reflect upon their struggle and revolt on the everyday level, which would further reflect upon the intersectionality within the women coal miners. In this attempt, the author has also tried to draw upon some comparison with the women miners and their saga from the Appalachian Mountains in North America.